Bacterial Vaginosis Associated With Preterm Premature Rupture of Membranes: A Case Report - Aliffudin Nuur; Indrahani Alwi; Aprilia Arifianti (Syntax Corporation, 2022)
Bacterial vaginosis is condition which caused by increasing production of vaginal mucus. Nearly one of five women in Indonesia are affected by bacterial vaginosis. More than thirty percent symptom recurrent in 1 years. A i23 iyears iold iwoman, ifirst itime ipregnant icoming ito iemergency idepartment iin iour ihospital. iShe icomplained iabout i32 iweeks igestational iage icame iout iblood ispot iand ifluid ifrom ibirth icanal isince i10 ihours iago. iShe iis igenerally iwell icondition, iwith ino iabdominal ipain ior ibirth icanal ipain. iPatient icomplains iitchy iand ireddish ivagina. iShe ialso ihave irecurrent iwhitish ihistory ipreviously iuntil inow. iShe ialso isays iwhitish iputrid ismells iand igrey icolored isomewhat. iSpeculum isterile iexamination, ilooked iwhite ito igray imucus iwith iPH i5, iWhiff itest i(+), iamin ites i(+), iNugent iscore i= i7. iFetal iultrasonography iexamination ishows ithe iamnion iare iwithin inormal iAFI i10 icm. iNitrazine itest i(+).We present a women with preterm premature rupture of membranes that caused by bacterial vaginosis. The mechanism of preterm labor are breakdown iof imembrane iintegrity icausing irupture i(due ito iinflammation iand ithe iaction iof ithe iprotease ienzymes), iand iinclude ithe irelease iof iendotoxin, iexotoxin iand iprostaglandin ithat istimulating icytokines. iThe iTwo ihypotheses iput iforward ifor ibacterial ivaginosis ion ipreterm ilabor, ifirst; iorganisms ithat imove iascending ito ithe iuterus iand isecondly, ibacterial ivaginosis iis ia imarker iof iintrauterine icolonization iby isimilar iorganisms. Eventhough bacterial vaginosis did not included sexually transmitted infection, but the impact to preterm pregnancy as well as sexually transmitted infection.